STUDIES ON MORPHOMETRY AND HYDROLOGY OF GANDHISAGAR RESERVOIR WITH SPECIAL REFERENCE TO ITS FISHERIES - RAO, K s; KARTHA, K N; GUPTA, D R; PANDYA, S S; IYER, H K (Fishery Technology, 2017)
Gandhisagar, the second largest reservoir of India is located in Mandsaur district of Madhya Pradesh at latitude 24Â° 44'N and longitude 75Â° 33'E at an altitude of 403.56m MSL in an orientation from NE to SE. It has an extensive water spread area of 66000 ha at full reservoir level with a maximum and mean depth of 49 .52 and 11. 73 m respectively. The maximum length and width of the reservoir are 112 and 16 km having a total shore line of 442 km. Details of catchment area, bathymetry, standard hydrological data giving water level relation of the basin to water spread area, volume and fish production and the bottom topographical details of 11 experimental fishing stations and 6 fish landing centres are discussed.